Morphodynamics of sandy embayed beaches from the Southwest Portugal rocky coast. - Gama, Cristina (2008)
This study compares five embayed sandy beaches (São Torpes, Furnas, Amoreira, Monte Clérigo and Arrifana) from the southwest Portugal rocky coast, between Sines and São Vicente capes. In order to analyze morphodynamics of these beaches were studied the volumetric active sediment changes, wave climate characteristics and propagation effects to nearshore for a period of two years. Major volumetric changes were largely associated with storm effects that caused berm and foredune retreat in the Furnas and Amoreira beaches. Obtained estimations of dimensionless fall velocity of São Torpes, Furnas, Amoreira and Arrifana beaches are characteristic of an intermediate morphodynamic stage with low tide terrace (ridge and runnel system), while Monte Clérigo beach is dissipative. The wave breaking height and beach configuration is responsible for different degrees of exposure to the dominant NW wave direction. The wave breaking height reduction is differently influenced by the wave diffraction, which is insignificant in the Amoreira and Monte Clérigo beaches. Comparison between real beach planform and predicted equilibrium configurations for these beaches suggests that the Arrifana beach represents a perfect example of a fully developed parabolic bay shape while, the other four beaches are not represented by any theoretical curve approach. This study shows that studied beaches morphdynamic behaviour is function of a complex equilibrium between the subaerial beach configuration, the ridge and runnel system, the longshore sedimentary distribution, the degree of exposure to the dominant NW wave direction and the storm incidence.